2018
DOI: 10.1007/s10529-018-2572-x
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus spp. impair the ability of Listeria monocytogenes FBUNT to adhere to and invade Caco-2 cells

Abstract: The studied Lactobacillus strains have protective effects against the adhesion and invasion of L. monocytogenes FBUNT. Alginate encapsulation of these bacteria improved gastrointestinal tolerance such that they could be further studied as potential probiotics against intestinal pathogenic bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The adhesion and invasion abilities of L. monocytogenes to Caco-2 cells are reduced when L. monocytogenes is co-cultured with Lactobacillus spp. [ 68 ], Lactobacillus rhamnoides [ 69 ], and L. plantarum [ 55 ]. Moroni et al observed that the adhesion and invasion ability of L. monocytogenes to colonocytes was reduced by Lactobacillus [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion and invasion abilities of L. monocytogenes to Caco-2 cells are reduced when L. monocytogenes is co-cultured with Lactobacillus spp. [ 68 ], Lactobacillus rhamnoides [ 69 ], and L. plantarum [ 55 ]. Moroni et al observed that the adhesion and invasion ability of L. monocytogenes to colonocytes was reduced by Lactobacillus [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Survival of passage through the challenging conditions in the digestive tract and adhesion to human cells are important for strains to show their health effects in the human gut. The resistance to such conditions is crucial, as exposure to bile salts causes dissociation of the lipid bilayer of cell membranes and disruption of the integrity of cells [45][46][47][48][49][50][51][52][53][54]. Consumption of approximately 1.0x10 6 to 1.0x10 10 viable cells per day is generally accepted as the minimum limit required in order to gain satisfactory probiotic functions in the intestine [15,[55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Studies also concluded that coaggregation, autoaggregation and adhesion abilities are strain specific. This specificity is determined by surface proteins, glycoproteins, teichoic acids and lipoteichoic acids, as well as S-layer proteins [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. The strains used in our study showed high rates of adhesion to intestinal epithelial cells (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective growthpromoting and protective effect of the oligosaccharide FOS in his study could be attributed to the preference of L. fermentum cells entrapped to FOS encapsulated. At a deeper level, 33 revealed that microencapsulation with oligosaccharides allowed viable L. fermentum cells to guarantee a high level for use as a probiotic during intestinal simulation, based on the usual effective dosage of 10 7 -10 9 CFU/ml.…”
Section: Survival Of Microencapsulated Cells Of 3 Probiotic Strains I...mentioning
confidence: 99%